PELAKSANAAN EVENT PETANG MEGANG DI KOTA PEKANBARU - Sonia Amrizal; Andi M. Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Pekanbaru has tourism potencial as nature tourism, cultural tourism, religious tourism and history tourism. Event Petang Megang held on the afternoon before welcoming the holy month of Ramadan. Because it, this research was conducted to find out how to implementation event Petang Megang di Kota Pekanbaru. Which is conducted by Dinas Kebudayaan dan Pariwisata Kota Pekanbaru to increase the number of tourist visits in pekanbaru city.This study aims to know how implementation Event Petang Megang as well as the intent and purpose implementation Event Petang Megang di Kota Pekanbaru.This research used descriptive qualitative method to examine the issues raised by analyzing implementation Event Petang Megang di Kota Pekanbaru. As for key informant in this research as many as five people involved as perpetrator of event,taken from the interview.While data collection techniques in this study using observation, interviews, and documentation.The result of this study show that implementation Event Petang Megang it’s been much different in the past because of the time that has been shortened and the of process of change in the activity at the time of the event, with the change in the implementation of this event on the afternoon of the past is the cultural preservation while at the present time it’s an Event petang Megang to preserve culture and as a cultural tourism.In the implementation of the Event Petang Megang there are several races that are catching the ducks, melayu song, and runway.So with the holding of the will increase the number of tourist arrivals in pekanbaru city to follow the Event Petang Megang.Petang Megang has become a flagship event in the city of pekanbaru so it must be preserved because this event is a legacy of the ancestors of the tribe melayu.Keywords : Event, Petang Megang, Tradition in Pekanbaru